Peran Media Sosial dalam Meningkatkan Partisipasi Politik Masyarakat di Desa Candirejo Kecamatan Biru-Biru Kabupaten Deli Serdang - Puji Chairunisa; Dewi Putri Batubara; Oktavia Anjelina Saragih; Julia Ivanna (Journal on Education, 2024)
This research discusses the role of social media in increasing community political participation in Candirejo village, Biru Biru subdistrict, Deli Serdang district. Social media is a potential tool for the government to shape public opinion and influence political participation. In the context of a democratic country like Indonesia, public opinion has a crucial role. because it is the basis for government functions, this research uses a qualitative descriptive method, the research stage is carried out by collecting data, interviews, observations and analysis, the results of the research show that social media plays a vital role in political participation and the formation of public opinion in the digital era, with an impact good and bad. Nevertheless, the government needs to monitor political activities in the modern social media era. Social media is not only a communication platform, but also a place for information seeking, discussion and networking. This research aims to find out how social media shapes political participation in society using a qualitative descriptive approach. The research results show that social media has a significant influence in engaging, connecting, and mobilizing political participation, although the receipt of political information via social media may vary between individuals.